PENGOLAHAN AIR SUMUR GALI YANG TERCEMAR BESI (FE) DAN MANGAN (MN): STUDI KASUS DI KELURAHAN KOYA TIMUR, KOTA JAYAPURA - Pamungkas, Akbar Ilham; Walukow, Auldry F.; Medyati, Novita; Mulyono, Sri; Mofu, Renold (Media Penelitian dan Pengembangan Kesehatan, 2023)
Clean water quality is influenced by groundwater pollution, this pollution results in a decrease in water quality so that it does not meet health requirements. The clean water quality standards are 0.2 mg / l for Fe and 0.1 mg / l for manganese. The city of Jayapura itself common pollution is iron (Fe) and manganese (Mn) in addition to other physical and chemical criteria. This pollution is because the soil in Jayapura tends to be swampy and calcareous. The study aimed to treatment of dug well water contaminated with Fe and Mn by bubble aerator method, electrolysis, and ion changer case study of community wells in East Koya Village, Jayapura City. This study used pure experiments of three treatments, namely bubble aerator, electrocoagulation, and ion changer with purposive sampling techniques. Test analysis using one-way Anova followed by Post Hoc test. The variant homogeneity test showed a p-value of 0.049 while the One-Way Anova test showed a significant difference in iron and manganese after treatment with a p-value of 0.000. However, what is effective in treatment iron and manganese contamination according to drinking water and clean water quality standards in accordance with Indonesian Minister of Health Regulation No. 2 of 2023 is an ion changer with a filtration duration of 90 minutes with an effectiveness in reducing Fe by 99.83% and Mn by 97%, while bubble aerators are only effective in treatment Mn filtration for 90 minutes with a decrease of 99%. The study concluded treatment of dug well water contaminated with Fe and Mn in accordance with clean water and drinking water quality standards is an ion changer.